'Cantavan tutti insieme ad una voce': Singing and Community in the Commedia*. (2nd January 2016) - Phillips-Robins, Helena
Abstract : This essay argues that in the Commedia song becomes a key means of shaping and expressing modes of communal being. The singing of In exitu Israel that marks the souls' arrival in Purgatorio and the performance of the Gloria that marks each soul's departure create multiple communities that stretch across time and space to encompass the purgatorial souls, the angelic hosts, and even the readers of the poem. I examine contemporary liturgical practices to suggest that the souls' sung arrival into purgatory evokes a particular liturgical procession and that Dante's treatment of word, music, and movement offers the reader an opportunity to partake in the communal dynamics of Purgatorio.